Upaya Meningkatkan Minat Belajar Menggunaan Media Gambar Pada Materi IPA - Islamiah; Faliyandra, Faisal (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The problem of science education in the context of Indonesia's national education is something that must be considered. Imagine that Indonesia has been ranked lowest in science scores on PISA since 2000. So this research will try to solve the problem of declining interest in learning in elementary school science subjects. This study uses Classroom Action Research (CAR) as a background for class problems, namely the decline in interest in learning science in grade II. The research subjects to be conducted were at the Nurul Yaqin Class II Madrasah Ibtidaiyah (MI) with a total of 13 students. The results of implementing this class action explain that; 1) using three action cycles; 2) the average of each cycle has an effective increase; 3) and also experiencing various problems that require improvement in each process. However, if you look at the overall results of the implementation of this image media, it can increase students' learning interest in class II elementary schools. This is because learning to use media images is very fun. For more details about the problems and research results will be explained in this paper.